En torno al dialecto de Acaya y sus colonias en la Magna Grecia (A proposito de un reciente libro de Alberto Giacomelli) (Minerva, 2019)
A book by A. Giacomelli provides occasion for this review-article where recent dialectological research on the inscriptions of Achaean colonies in Magna Graecia is critically surveyed. The problems addressed include some idiosyncratic uses of and , linguistic contact in Magna Graecia (pre-Achaean remnants, convergence, Doric Koiná), nom. H(έ)ρακλες, etc. Special attention is paid to the debate of whether the Achaean dialect originally belonged in the Doris mitior with a system of seven long vowels, as the evidence furnished by recent inscriptions in Peloponnesian Achaea seems to suggest, or -to judge from the scanty data available for the colonies- in the Doris severior with only five long vowels. Contrary to current opinion, it is the mother city which must have preserved the original situation.